Alterações morfofisiológicas em feijoa (Acca sellowiana) sob diferentes níveis de sombreamento - Silva, Luana Ribeiro (2020)
Plant species have specific requirements regarding the luminous availability necessary for their development. In this context, the heterogeneity in the availability of light commonly present in natural growth environments can cause different morphological, anatomical and physiological responses in plants, thus constituting mechanisms of acclimatization and phenotypic alteration due to the variation in available light. Acca sellowiana has economic, medicinal and ecological importance, however, ecophysiological information about this species is still scarce. Under the hypothesis of acclimation of feijoa under different conditions of light availability, growth parameters, biomass accumulation and allocation, leaf morphophysiological parameters, gas exchange and chlorophyll a flowering parameters were evaluated. The seedlings were grown for 21 months in four levels of shade: 0% (full sun), 30%, 50% and 80% interception of solar radiation.The accumulation in total dry mass was significantly higher in seedlings grown under full sun and 30% shade during the study period. The largest leaf area and specific leaf area were obtained from seedlings grown under 80% shade, and relatively smaller in full sun, although in this treatment the largest number of leaves was observed. For photosynthetic pigments, there was a significant difference only for carotenoid ter and carotenoid / total chlorophyll ratio, which was higher in plants under full sun. The net assimilation of CO2 and the electron transport rate was limited under 80% shading. There was an increase in stomatal conductance and perspiration rate under full sun and 30% of shading, while the intercellular CO2 concentration was greater in 80% of shading. The thickest leaf blade was observed in leaves under conditions of full sun and 30% shading.Feijoa has acclimatization mechanisms mainly in relation to changes in leaf morphophysiology and anatomy. In view of the factors evidenced in the present study, it is suggested the use and cultivation of this species in conditions of full sun at 30% shading, thus denoting the requirement of solar radiation for its optimum development, and therefore, being a characteristic of heliophile species. Allied to this, the ability of feijoa to support shading was identified in this study and this can be directly related to acclimatization strategies, although under reduced light availability its development is incipient.